Overcoming blood brain barrier with a dual purpose Temozolomide loaded Lactoferrin nanoparticles for combating glioma (SERP-17-12433) - Sonali Kumari (Nature Portfolio, 2017)
Abstract Targeted delivery of drugs to the brain is challenging due to the restricted permeability across the blood brain barrier (BBB). Gliomas are devastating cancers and their positive treatment outcome using Temozolomide (TMZ) is limited due to its short plasma half-life, systemic toxicity and limited access through the blood-brain barrier (BBB). Nanoparticles made of Lactoferrin (Lf) protein, have been shown to enhance the pharmacological properties of drugs. Here, we report the specific ability of Lf nanoparticles to cross BBB and target over-expressed Lf receptors on glioma for enhanced TMZ delivery. TMZ-loaded Lf nanoparticles (TMZ-LfNPs) were prepared by our previously reported sol-oil method. While the Lf protein in the NP matrix aids in transcytosis across the BBB and preferential tumor cell uptake, the pH responsiveness leads to TMZ release exclusively in the tumor microenvironment. Delivery through LfNPs results in an enhanced and sustained intracellular concentration of TMZ in GL261 cells in vitro along with improving its in vivo pharmacokinetics and brain accumulation. TMZ-LfNPs treatment results in a significant reduction of tumor volume, higher tumor cell apoptosis and improved median survival in glioma bearing mice. These results demonstrate that LfNPs present an efficient TMZ delivery platform for an effective treatment of gliomas.